2023
DOI: 10.3390/molecules28020851
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Prolidase (rhPEPD) Induces Wound Healing in Experimental Model of Inflammation through Activation of EGFR Signalling in Fibroblasts

Abstract: The potential of recombinant human prolidase (rhPEPD) to induce wound healing in an experimental model of IL-1β-induced inflammation in human fibroblasts was studied. It was found that rhPEPD significantly increased cell proliferation and viability, as well as the expression of the epidermal growth factor receptor (EGFR) and downstream signaling proteins, such as phosphorylated PI3K, AKT, and mTOR, in the studied model. Moreover, rhPEPD upregulated the expression of the β1 integrin receptor and its downstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…This tyrosine kinase enzyme phosphorylates specific intracellular substrates, initiating signaling pathways that ultimately result in cellular proliferation (43). According to previous studies, EGFR promotes cell proliferation, angiogenesis, and invasion (44,45). The motility of keratinocyte stem cells, driven by the EGFR-collagen type XVII α1 (COL17A1) axis, plays a crucial role in epidermal regeneration, suggesting a promising therapeutic strategy for addressing defective skin regeneration (46).…”
Section: Discussionmentioning
confidence: 99%
“…This tyrosine kinase enzyme phosphorylates specific intracellular substrates, initiating signaling pathways that ultimately result in cellular proliferation (43). According to previous studies, EGFR promotes cell proliferation, angiogenesis, and invasion (44,45). The motility of keratinocyte stem cells, driven by the EGFR-collagen type XVII α1 (COL17A1) axis, plays a crucial role in epidermal regeneration, suggesting a promising therapeutic strategy for addressing defective skin regeneration (46).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports also show increased prolidase mRNA levels and higher enzymatic activity in wound fluid and scar tissues ( 16 , 17 ). Furthermore, a recent study showed that recombinant human prolidase induces cell growth, proliferation, migration, and collagen biosynthesis in human fibroblasts ( 18 ). However, the mechanisms and pathways that regulate prolidase expression are poorly understood.…”
mentioning
confidence: 99%